Memory for emotional events: The role of time of testing and type of test - Brust, Priscila Goergen; Pontifícia Universidade Católica do Rio Grande do Sul (Pontificia Universidad Javeriana, 2011)
The impact of emotion on memory performance is widely debated in the scientific literature. In the present paper, the relation between emotion and memory was addressed in three experiments using the Slideshow Procedure. In the first experiment, 128 participants’ memory was tested for one of two versions of the Procedure (arousal or neutral) through free recall. In the second experiment, 75 participants were asked to recall the information of the arousal version immediately after or one week after watching it. In the third experiment, 75 participants watched the arousal version and answered either a free recall or a recognition test one week after. The results suggested that memory for arousal events is better when tested immediately after the stimuli using free recall.